Editoriale 21 - Paolo Di Nardo (And, 2012)
At the end of the eighteenth century Quatremére de Quincy made a distinction between 'architectural composition' and 'architectural conception', noting that the latter is an operation of the spirit that can be expressed even with a sketch.